Noninvasive evaluation of skeletal muscle mitochondrial capacity with near-infrared spectroscopy: correcting for blood volume changes - Ryan, Terence E. (American Physiological Society, 2012)
Near-infrared spectroscopy (NIRS) is a well-known method used to measure muscle oxygenation and hemodynamics in vivo. The application of arterial occlusions allows for the assessment of muscle oxygen consumption (mV̇o(2)) using NIRS. The aim of this study was to measure skeletal muscle mitochondrial capacity using blood volume-corrected NIRS signals that represent oxygenated hemoglobin/myoglobin (O(2)Hb) and deoxygenated hemoglobin/myoglobin (HHb). We also assessed the reliability and reproducibility of NIRS measurements of resting oxygen consumption and mitochondrial capacity. Twenty-four subjects, including four with chronic spinal cord injury, were tested using either the vastus lateralis or gastrocnemius muscles. Ten healthy, able-bodied subjects were tested on two occasions within a period of 7 days to assess the reliability and reproducibility. NIRS signals were corrected for blood volume changes using three different methods. Resting oxygen consumption had a mean coefficient of variation (CV) of 2.4% (range 1–32%). The recovery of oxygen consumption (mV̇o(2)) after electrical stimulation at 4 Hz was fit to an exponential curve, which represents mitochondrial capacity. The time constant for the recovery of mV̇o(2) was reproducible with a mean CV of 10% (range 1–22%) only when correcting for blood volume changes. We also examined the effects of adipose tissue thickness on measurements of mV̇o(2). We found the mV̇o(2) measurements using absolute units to be influenced by adipose tissue thickness (ATT), and this relationship was removed when an ischemic calibration was performed, supporting its use to compare mV̇o(2) between individuals of varying ATT. In conclusion, in vivo oxidative capacity can be assessed using blood volume-corrected NIRS signals with a high degree of reliability and reproducibility.